2003
DOI: 10.1046/j.1439-0396.2003.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Taurine status in normal dogs fed a commercial diet associated with taurine deficiency and dilated cardiomyopathy

Abstract: Taurine (Tau) deficiencies have been associated with the feeding of commercial lamb-meal and rice diets to dogs. We hypothesized that the poor digestibility of some lamb-meals may limit sulphur amino acids availability for Tau synthesis and/or increase of Tau degradation in the gut. Growing dogs were fed either a lamb-meal-based (Diet A) or poultry by-product-based (Diet B) commercial diet. Plasma, whole blood and urinary Tau were measured for 22 weeks. Plasma and whole blood Tau concentrations were similar be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Taurine is obligatorily lost in urine and in bile acids that are not recovered by means of enterohepatic circulation. 36,37 In taurine-deficient cats, urinary taurine losses are low because of the low concentration of taurine in plasma filtrate and the upregulation of renal tubular taurine transporters. Extraordinary urinary taurine losses cannot be ruled out as a cause for the present observations, in that as much as the urine taurine-to-creatinine ratio is an indicator of urine taurine loss, 35 this ratio appeared to be too high in some dogs in the present study, given their plasma taurine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is obligatorily lost in urine and in bile acids that are not recovered by means of enterohepatic circulation. 36,37 In taurine-deficient cats, urinary taurine losses are low because of the low concentration of taurine in plasma filtrate and the upregulation of renal tubular taurine transporters. Extraordinary urinary taurine losses cannot be ruled out as a cause for the present observations, in that as much as the urine taurine-to-creatinine ratio is an indicator of urine taurine loss, 35 this ratio appeared to be too high in some dogs in the present study, given their plasma taurine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the minimum requirement for taurine in dogs fed normal diets is zero (NRC, 2006). Although beneficial effects of additional taurine on dilated cardiomyopathy have been observed in dogs (Kittleson et al, 1997;Tôrres et al, 2003), particularly large breeds (Backus et al, 2006), no recommendations were suggested. The dose was mostly chosen to normalise plasma taurine.…”
Section: Dogsmentioning
confidence: 99%
“…Studies have not consistently shown an association between dietary and circulating taurine concentrations [37]. However, taurine deficiency has been associated with lamb meal and rice based diets and high fiber diets [37][38][39][40][41]. Thus, dietary taurine availability or digestibility may play a role [42].…”
Section: Taurinementioning
confidence: 99%